Особенности токсического действия лакокрасочных материалов при различных путях поступления - Крючкова, Н.Н.; Половинкин, Л.В.; Соболь, Ю.А. (Актуальні проблеми транспортної медицини, 2009)
Наводяться результати порівняльної оцінки токсичності і небезпеки водно дисперсійних і органорозчинних лакофарбових матеріалів при різних шляхах надходження: внутрішньошлунковому, нашкірному, інгаляційному. Дана оцінка сенсибілізуючої дії різних видів лакофарбових композицій, визначені їх класи небезпеки, подразнюючої дії і алергенної активності. Встановлені критерії, що зумовлюють гігієнічну безпеку лакофарбових матеріалів. In clause the results toxicological of research of a paint and varnish of materials on water and organic solvents are resulted. The results of a comparative toxicological evaluation and danger of paint and varnish materials on water and organic solvents are resulted at various ways of receipt: in a stomach, on a skin and at inhalation. The estimation of allergic action various of paint and varnish materials is given, the classes of danger and irritating action and allergy of activity are determined. The criteria causing hygienic safety of paint and varnish materials are determined.